Analysis of Trail Runner Performance Based on Coros Wearable Device Data - Muhammad Ghufron Faqih; Anggit Wicaksono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study analyzed the performance of an ultra-trail runner in two races (62 km and 50 km) using a wearable device (Coros Pace 3). The subject was a 26-year-old male runner with more than four years of experience in ultra-trail running. Parameters examined were pace, heart rate (HR), and elevation. The results showed that elevation strongly influenced both pace and HR, with more conservative pacing observed in the 62 km race and more aggressive early effort in the 50 km race. The analysis was conducted descriptively and through a regression model with elevation control as a covariate. The results showed an oscillatory pacing pattern influenced by elevation contours, with HR increasing significantly in uphill segments. These findings highlight the importance of adaptive pacing strategies  based on elevation profiles and suggest that wearable data can provide practical insights for training and competition. Runners need to know the details of the race track, including distance and elevation, and train in conditions similar to the actual track so that physiological adaptations occur and they can achieve their best performance during the race.